2022
DOI: 10.1111/jcal.12674
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self‐assessment and performance in learning TPACK: Are self‐assessments a good way to support preservice teachers' learning?

Abstract: Background To purposefully integrate information and communication technologies (ICT) into contemporary teaching, teachers must have complex technological, pedagogical and content‐related knowledge (TPACK). TPACK could be fostered through diverse learning environments such as working in a makerspace as part of university teacher training. The development of TPACK in (preservice) teachers depends on how effectively they can assess their own knowledge and adapt their own learning process. Self‐assessment tools c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
(88 reference statements)
0
16
0
3
Order By: Relevance
“…The second block covers the media project work in the makerspace. The task of the project is to design and implement a teaching‐learning material to be used in biology or psychology lessons in school (Lukas et al, 2020; Max, Lukas et al, 2020; Max et al, 2022), in the sense of STEAM‐related artefacts (Jones et al, 2020) (Example 1 to 3 in Appendix A). The development of the materials takes place in the university's pedagogical makerspace (Appendix B, picture of makerspace).…”
Section: Methodsmentioning
confidence: 99%
“…The second block covers the media project work in the makerspace. The task of the project is to design and implement a teaching‐learning material to be used in biology or psychology lessons in school (Lukas et al, 2020; Max, Lukas et al, 2020; Max et al, 2022), in the sense of STEAM‐related artefacts (Jones et al, 2020) (Example 1 to 3 in Appendix A). The development of the materials takes place in the university's pedagogical makerspace (Appendix B, picture of makerspace).…”
Section: Methodsmentioning
confidence: 99%
“…However, self-reports do not necessarily correspond to the results of more objective assessment methods, such as knowledge tests [32] or enacted TPACK measures [23,33,34]. There are indications that the pre-service teachers' ability for self-assessment decreases with increasing task complexity (e.g., with increasing reference to teaching practice) [35]. Additionally, there remains a gap between TPACK acquired at the university and enacted TPACK in practice [15].…”
Section: Tpack Framework and Tpack Measurementmentioning
confidence: 99%
“…To appropriately serve its function, students' self-assessments need to be accurate (Ernst et al, 2023). Regarding RQ2, numerous students often exhibit a tendency to inaccurately evaluate their own abilities (Max et al, 2022). Ernst et al (2023) conducted a comprehensive literature review, revealing that students' relative accuracy remained notably low and exhibited a negative correlation with students' overconfidence.…”
Section: Challenges Of Self-assessmentmentioning
confidence: 99%
“…often attained above-average scores. Furthermore, it was established that students in the early stages of their academic journey (Zhang & Zhang, 2022) or those with poorer academic outcomes tend to overestimate their own performance and level of knowledge (Carroll, 2020;Max et al, 2022). Additionally, Lew et al (2010) found that students' self-assessment ability does not improve over the course of a semester, and that more academically competent students have more accurate self-assessments of their knowledge than less competent students.…”
Section: Challenges Of Self-assessmentmentioning
confidence: 99%
See 1 more Smart Citation